Evaluation of the Implementation of Occupational Safety and Health Management Systems in Building Construction Projects in the Public Works, Spatial Planning and Land Affairs Agency of Kepulauan Riau Province - Kurniawan, Nuzul Kurniawan; Ngaliman Ngaliman; Ana Faizah (International Journal of Management Research and Economics, 2024)
Work accidents in every construction project are increasing in government projects, so an evaluation of the implementation of the Occupational Safety and Health Management System (SMK3) is needed in companies, particularly those with a construction service budget of less than 15 billion, which are categorised as small companies so that these companies are often ignored in the evaluation of the implementation of the occupational safety and health management system. In addition, each company must provide a conceptual design of the construction safety management system to guide the company when winning the tender. The many challenges and obstacles in the Construction Safety Management System (SMKK) cannot be separated from companies' lack of understanding and desire to implement the occupational safety and health management system, which is the output in every implementation of construction project work. Therefore, it is necessary to evaluate the company by referring to the construction safety management system design and the results of the occupational safety and health management system implementation that the company has carried out. On the other hand, only a few studies have evaluated using the CIPP method in assessing occupational safety and health management systems based on context, input, process, and product (CIPP). The research method used is a descriptive research design that uses observation, interviews, and structured questionnaires through purposive sampling to take research samples so researchers can better organise research subjects. In addition, the study uses a combination of qualitative research methods equipped with quantitative data to obtain more comprehensive data from the evaluation research on implementing the occupational safety and health management system in companies. Based on the results of the study that were able to be identified by researchers, the problems of companies and workers occurred more due to the lack of commitment to Occupational Health and Safety (K3) and the implementation of the occupational health and safety work culture in construction projects, both commitment from the company and commitment from workers to the occupational health and safety, which will have an impact on the implementation of occupational health and safety in work culture.